A lógica matemática da arte ornamental: uma relação de equivalência a partir da estrutura atômica dos cristais - Pantaleão, Lucas Farinelli; Pinheiro, Olimpio José [UNESP] (My University, 2012)
Based in aesthetic relationship between concepts of content and form intends to establish an relationship of analogy between ornaments and crystals. With the objective of building an theoretical investigation of relating the dynamics that happens in the crystals´ atoms to the symmetrical intervals of the ornamental patterns, it tries to draw a reasoning line that is going from the ‘Idea’ of Plato and ‘poiésis’ of Aristotle, until Hegel's philosophical enlargement, that admits the aesthetics as a science of the art integrated in a metaphysical process. Inherent to this question intends, in interrelation terms between aesthetics and metaphysics, content as being intelligent beginning, energy, and form as primitive element, matter, in order to evidence the possibility to calculate the same present symmetries in the ornamental arts like in the nature.

Fundamentado na conceituação estética entre os conceitos de conteúdo e forma pretende-se estabelecer uma relação de analogia entre ornamentos e cristais. Com o objetivo de construir uma investigação de cunho teórico relacionando a dinâmica que ocorre nos átomos dos cristais aos intervalos simétricos dos padrões ornamentais, procura-se traçar uma linha de raciocínio que vai desde a Idéia de Platão e a poiésis aristotélica, até a ampliação filosófica de Hegel, que admite a estética como uma ciência da arte integrada num processo metafísico. Inerente a este questionamento propõe-se, em termos de inter-relação entre estética e metafísica, conteúdo como sendo princípio inteligente, energia, e forma como elemento primitivo, matéria, a fim de evidenciar a possibilidade de calcular as mesmas simetrias presentes tanto nas artes ornamentais como na natureza.
Keywords: Crystals; Ornament; Aesthetic; Content / Form; Metaphysical; Ornamento; Estética; Conteúdo-Forma; Cristais; Design